El ocultamiento de los bienes en la sociedad conyugal: la inequidad entre el daño, los perjuicios y la sanción del artículo 1824 del código civil - Ruíz Rueda, Carmen Cecilia (Universidad Antonio Nariño, 2023)
Through this research study, the legal scenario that is derived from the application of article 1824 of the Civil Code in the reparation of the damages caused to the innocent spouse by the concealment of the property of the conjugal society is analyzed; where for the origin of the respective sanction a probative burden of great complexity corresponding to the intent is established that in most cases it is not possible to demonstrate; what bases the proposal of a joint application with the article 2341 in the judicial praxis relative to the requirements that must be observed in the compensation of damages derived from the conduct of the spouse that tries to hide or distract the goods that correspond to the conjugal society.